THE INFLUENCE OF THE IMPLEMENTATION OF E-ATTENDANCE ON THE DISCIPLINE OF STATE CIVIL APPARATUS IN THE REGIONAL PERSONNEL AGENCY OF GORONTALO PROVINCE - Alhusna A. Pontoh (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research aims to determine the effect of the implementation of e-attendance on the discipline of State Civil Apparatus (ASN) at the Regional Personnel Agency of Gorontalo Province. This research uses a quantitative approach with a sample of 80 State Civil Apparatus members. The data types in this study are both primary and secondary. Data collection was done by distributing questionnaires to employees at the Regional Personnel Agency of Gorontalo Province. Data analysis was performed using simple linear regression analysis, with data processing conducted using SPSS 25. The results of this research show that e-attendance has a positive effect on the discipline of State Civil Apparatus in the Regional Personnel Agency of Gorontalo Province, with an R Square value of 0.608, meaning that 60.8% of ASN discipline is influenced by e-attendance, while the remaining 39.2% is influenced by variables not included in this study.